Kendi Kendine İlaç Kullanımı ve Sağlık Okuryazarlığı İle İlgili Özelliklerin Saptanması - şenlik, zeynep belma (Turkey Health Literacy Journal, 2023)
To determine the self-medication use and health literacy level of individuals who receive health services from family medicine units in Ankara.This cross-sectional study was carried out with 355 people over the age of 18 who applied to the family medicine unit for any reason and agreed to participate in the study. As a data source, the questionnaire form was applied face to face. The first part of the questionnaire includes questions about socio-demographic characteristics, the second part includes questions about health status and self-medication, and the third part includes the Turkish Health Literacy Scale.The frequency of self-medication of the participants was 27.9%, the frequency of self-medication in the last 1 year was 24.8%, and the frequency of self-medication in the last 1 month was 19.2%. 15.2% of the participants stated that they did not read the prospectus of the drugs. 53.5% of the participants were inadequate, 19.4% had problems, 18.6% were adequate, and 8.5% had excellent health literacy. The frequency of self-medication by the participants is 3.0 times higher for women, 5.9 times for chronic disease, 5.6 times for reading a prospectus, 8.8 times for health problems lasting less than two weeks, after consulting a pharmacist when there are health problems lasting less than two weeks. Using herbal-traditional methods when there are health problems lasting less than two weeks 4.1 times, using herbal-traditional methods 6.7 times, keeping medication at home with the thought that it will be needed in the future 5.2 times, recommending medication to family members 7, It increases 3 times.
Keywords: Self-medication, Health Literacy, Behaviors Affecting Health